CAMINHOS CRUZADOS: MARXISMO E NACIONALISMO NO BRASIL E NO PERU (1928-1964) - Kaysel, André (CEDEC, 2019)
This article addresses the relationship between communist-oriented marxism and popular nationalism in two contexts: Brazil, between the 1950s and the 1960s, and Peru, between the 1920s and the 1930s. I start from the hypothesis that this two concurrent ideological tendencies shaped the Latin American leftist immaginary, from the late 1920s to the Cuban Revolution. I shall demonstrate how the relationship between communists and nationalists followed opposite patherns in both cases: going from hostility to alliance in the Brazilian context, and evolving from a common origin to antagonism in Peru. I will explain this crossed paths appilling to both internal and external differences in conjunctures, especially concerning the communist movement. With this comparison, I seek to question the “theory of populism”, which sought to explain the defeat of Brazil’s left in 1964 because of the convergence between communists and nationalists.

Este artigo aborda as relações entre o marxismo de matriz comunista e o nacionalismo popular em dois contextos: o Brasil, entre as décadas de 1950 e 1960, e o Peru, entre 1920 e 1930. Parto da hipótese de que foram essas duas correntes ideológicas concorrentes que, no período que vai do final dos anos 1920 até a Revolução Cubana, plasmaram o universo ideológico das esquerdas latino-americanas. Procurarei demonstrar como a relação entre comunistas e nacionalistas seguiu padrões opostos nos dois casos: do conflito à aliança, no contexto brasileiro, e de uma origem comum ao antagonismo, no peruano. Explicarei esses padrões divergentes, tanto pelas diferenças entre os contextos nacionais, como pelo distinto contexto internacional, em particular no que se refere ao movimento comunista. Com essa pesquisa comparada, procuro submeter à crítica as formulações da chamada “teoria do populismo”, que procurou explicar a derrota da esquerda brasileira em 1964 pela convergência entre comunistas e nacionalistas.
CROSSED PATHS: MARXISM AND NATIONALISM IN BRAZIL AND PERU (1928-1964)
Keywords: Marxism; Nationalism; Populism; Brazil; Peru; Marxismo; Nacionalismo; Populismo; Brasil; Peru